2022
DOI: 10.1016/j.cmi.2021.09.030
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of ibrexafungerp against Candida species isolated from blood cultures. Determination of wild-type populations using the EUCAST method

Abstract: In vitro activity of ibrexafungerp against Candida species isolated from blood cultures. Determination of wild type populations using the EUCAST method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…In both studies, ibrexafungerp displayed remarkably lower MICs than micafungin against C. parapsilosis . Although Mesquida et al. (2022) did not differentiate among C. parapsilosis species complex, they also reported lower MICs for ibrexafungerp than for echinocandins.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In both studies, ibrexafungerp displayed remarkably lower MICs than micafungin against C. parapsilosis . Although Mesquida et al. (2022) did not differentiate among C. parapsilosis species complex, they also reported lower MICs for ibrexafungerp than for echinocandins.…”
Section: Discussionmentioning
confidence: 82%
“…Although there are no clinical breakpoints (CBPs) or ECVs available for ibrexafungerp, the study by Mesquida et al. (2022) as well as the present work have proposed WTULs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The triterpenoid ibrexafungerp, a new class of glucan synthase inhibitor currently being evaluated in various phase III trials, has shown excellent bioavailability after oral intake [ 43 ]; this drug may eventually be a good alternative when the use of azoles or echinocandins is contraindicated for any reason. We found that all isolates here tested, including those showing resistance to fluconazole and/or echinocandins, were considered ibrexafungerp wild type, which is in line with the high activity of this drug against isolates from blood and other clinical sources [ 27 ]. Clonal outbreaks of fluconazole-resistant C. parapsilosis isolates have been reported in different hospitals [ 44 ].…”
Section: Discussionmentioning
confidence: 84%
“…Isolates were categorized as resistant, susceptible, wild type, or non-wild-type according to clinical breakpoints or tentative epidemiological cutoff values (ECOFFs) provided by EUCAST [ 25 ]. Since there are no available clinical breakpoints for isavuconazole and ibrexafungerp, we used previously proposed tentative ECOFFs or wild-type upper limits [ 26 , 27 ]. All C. krusei isolates were considered intrinsically resistant to fluconazole.…”
Section: Methodsmentioning
confidence: 99%